Neurobehavioral and biochemical features of a mouse model for Parkinson’s disease. - Lee, Elianna Shu Hui. (2012)
Parkinson’s disease (PD) is a common age-related neurodegenerative disorder, characterized by degradation of dopaminergic neurons. The cardinal signs of PD are mainly motor dysfunctions. Non-motor symptoms, including anxiety and depression, which often precede motor symptoms, may also manifest. These behavioral phenotypes are commonly investigated through mice models. Due to widespread prevalence and early manifestation in patients, the role of non-motor symptoms is increasingly important in understanding the onset of PD. We aimed to characterize the onset of non-motor symptoms, in relation to the motor disorders, within a transgenic mouse model of PD. A longitudinal study of anxiety- and depression-like behaviors in mice was done through elevated plus maze and forced swim test. Results showed decreasing levels of anxiety-like behavior between ages 4 to 14 months while the level of depression-like behavior peaked in 4 and 12 months old mice. However, as concomitant increase in locomotion was observed between 4 to 14 months old mice, studies with other models of anxiety and depression may be necessary. No differences in anxiety- and depression-like behaviors were observed between transgenic and non-transgenic mice. Nevertheless, our findings coincide with reported age-associated trends and provided an insight into the correlation of anxiety and depression with PD.